건설신기술의 경제적 파급효과 분석 - 백남종; 박환표; 이교선; Paek, Nam-Jong; Park, Hwan-Pyo; Lee, Kyo-Sun (한국건설관리학회 논문집, 12(1), 2011)
The Construction New Excellent Technology was introduced to promote the development of domestic construction technology and enhance national competitiveness, by inspiring the development desire of technology developers in 1989. Domestic Construction New Excellent Technology is first introduced in 1989, the total 596 cases were assigned to the new technology and it was used the construction site. Also, it was achieved the quantitative performance of thirty-hundred applications and was effected to the domestic construction industry. However, the systematic analysis about the introduction effects of Construction New Excellent Technology are none. Therefore, the quantitative analysis of economic effects in construction industry have to a justification in according to operation of Construction New Excellent Technology system and verification of superiority. And then, the Construction New Excellent Technology system needs a developing base in the future. In this study, The Economic Impacts of Construction New Excellent Technology were analyzed in quantitatively such as a cost savings effects, the employment effects, the effects on Value-added, the import substitution effects due to use of Construction New Excellent Technology. This study will be used promotion of economics and superiority in the Construction New Excellent Technology. 우리나라는 1989년 기술개발자의 개발의욕을 고취시킴으로써 국내 건설기술의 발전을 도모하고, 국가경쟁력 등을 제고하기 위하여 건설신기술 지정제도를 도입하였다. 국내 건설신기술제도가 1989년 최초 도입되어 2009년 12월 31일까지 총 596건의 건설기술이 신기술로 지정되어 건설현장에 총 3만여회 이상 활용되는 등 양적 성과를 거두었고, 국내 건설산업에 직 간접적인 영향을 미치고 있으나, 건설신기술제도의 도입 효과에 대한 체계적인 분석은 이루어지지 않고 있다. 이에 건설신기술제도 도입 이후 건설현장에 활용되었던 양적 성과 외에 건설산업에 직 간접적으로 영향을 미친 경제적 파급효과를 정량적으로 분석함으로써 동 제도의 운영에 따른 당위성을 확보하고 우수성을 검증하여 동 제도가 향후 지속적으로 발전할 수 있는 기틀을 마련할 필요가 있다. 본 연구는 건설신기술 사용으로 인한 공사비절감액, 공사비절감으로 인한 타 산업 비용절감효과, 취업유발효과, 부가가치 유발효과, 수입대체효과 등 건설신기술의 경제적 파급효과를 정량적으로 분석하였다. 이러한 연구결과는 건설신기술의 경제성과 우수성을 널리 홍보하고, 활용촉진을 도모하는데 활용할 수 있을 것이다.